Plants dispersed by a non‐frugivorous migrant change throughout the annual cycle - Urgyán, Renáta; Lukács, Balázs A.; Fekete, Réka; Molnár V., Attila; Nagy, András; Vincze, Orsolya; Green, Andy J.; Lovas‐Kiss, Ádám (Global ecology and biogeography, 2023)
Aim Migratory waterfowl are important endozoochory vectors for a range of plants lacking fleshy fruits. Our aim was to study the critical question of how endozoochory rates change throughout the annual cycle, and how this relates to plant life‐form and phenology. Location Lake Velence, Hungary. Time period 2017–2018. Major taxa studied Mallard (Anas platyrhynchos), Angiospermae, Charophyta. Methods We studied waterfowl endozoochory, quantifying seeds and other diaspores dispersed by mallards by collecting faecal samples monthly (ntotal = 670) at a Hungarian lake. We tested the germinability of all seeds recovered from the faecal samples. Main conclusions We extracted 5,760 seeds representing 35 plant taxa from mallard faecal samples, and 40% of these seeds germinated successfully following gut passage. We found major differences between seasons in the species composition of the seeds recovered. The peak in species diversity and in abundance of terrestrial seeds coincided with the spring migration of mallards. Importantly, endozoochory was only strongly synchronized with seed production in submerged, but not in emergent or terrestrial plants, illustrating the potential for endozoochory of seeds ingested from the soil seed bank. Overall, our results suggest that endozoochory by migratory waterfowl is a strong and underestimated driver of plant distributions, and is likely to facilitate plant range shifts under climate change, and after introduction of alien species.